'Voxelization' of Alderson-Rando phantom for use in numerical dose measuring - Santos, A. M.; Vieira, J. W. (Cellular and Molecular Biology, 2009)
The use of computational models of the human body (anthropomorphic phantoms) assists in the estimation of the dose absorbed in organs or tissues of people exposed to sources of radiation which are external or internal to them. Nowadays, more realistic anthropomorphic phantoms are based on volume elements, well-known as voxels, and they are constructed from real images obtained through the scanning of people by Computed Tomography (CT) or Magnetic Resonance Imaging (MRI). The existence of artifacts in original images CT or MRI indicates the necessity of utilizing filtering processes before segmentation with the purpose of eliminating noises, improving contrasts and also to detect contours of organs regions. This study presents the methodology used for the creation of a phantom of voxels from tomographic images of Alderson-Rando (AR) physical phantom and the development of a computational model of exposure formed by phantoms resulting from "voxelization" of AR connected to Monte Carlo EGS4 code, added by algorithms to simulate radioactive sources in internal dose measuring.